Assessment of alveolar bone loss in orthodontic cases in Mosul City in 20-23 year old males - Zaid B Al-Dewachi (University of Mosul, College of Dentistry, 2004)
This study was undertaken to design the relationship between different orthodontic cases and amount of bone level loss. The study sample consisted of 72 male students (20-23 years old) classified into 3 groups: Control group with normal over jet and overbite, over jet group with at least 8 mm, and overbite group with at least 6 mm. The results showed a significant reduction of bone height in upper and lower incisors in malocclusion group at significant level 0.01 if it is compared with normal group bone level.